2020
DOI: 10.1371/journal.pone.0231430
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine leakage from perforin-burst extracellular vesicles inhibits perforin secretion by cytotoxic T-lymphocytes

Abstract: Extracellular vesicles (EVs) in the tumor microenvironment facilitate intercellular communication. Cancer cell-derived EVs act as an immunosuppressor by transporting cargos and presenting transmembrane proteins. By contrast, CD8+ cytotoxic T-lymphocytes (CTLs) exert anti-cancer cytotoxicity via the pore-forming protein perforin. Here, we hypothesize that although EVs are destroyed by perforin, cancer cell-derived EVs might possess mechanisms that enable them to avoid this destruction. We used a breast cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…The existence of intermediate metabolites of purine and pyrimidine metabolism in sEVs has already been reported. For example, sEVs derived from a breast cancer cell line were reported to have high concentrations of uridine and guanosine [ 37 ]. In addition, it has been reported that sEVs derived from head and neck squamous cell carcinoma cell lines and plasma from patients also contain intermediates for purine metabolism, which exhibit an immunosuppressive effect [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of intermediate metabolites of purine and pyrimidine metabolism in sEVs has already been reported. For example, sEVs derived from a breast cancer cell line were reported to have high concentrations of uridine and guanosine [ 37 ]. In addition, it has been reported that sEVs derived from head and neck squamous cell carcinoma cell lines and plasma from patients also contain intermediates for purine metabolism, which exhibit an immunosuppressive effect [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cationic metabolites were measured using LC-MS, as described previously [ 37 ]. Briefly, LC-MS analysis was performed using an Agilent 1290 Infinity LC system (Agilent Technologies, Santa Clara, CA, USA) equipped with a Q Exactive Orbitrap MS system.…”
Section: Methodsmentioning
confidence: 99%
“…On this aspect, there is a wide consensus. Indeed, ADO, via the interactions with P1 receptors [ 75 ], exhibits an indirect “protective” role on tumors by affecting the function of almost all cells of the immune system, including MCs and B, CD8 + CT, NK [ 50 , 58 , 60 , 64 ], and also Treg lymphocytes, of which ADO promotes the immune-suppressive activity [ 47 ]. Since it is even more evident that chronic inflammation may contribute to about 25% of human cancers [ 76 ], the overall behavior of TME/EV purines and enzymes is similar to that of the same compounds in inflammatory conditions [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other findings would also suggest ADO-induced immunosuppression via EV contribution. Thus, Tadokoro et al [ 58 ] showed that EVs secreted by cell lines of breast cancer are disrupted by perforin, a pore-forming protein liberated by CD8 + cytotoxic lymphocytes (CTLs), when activated by the known cytokine interferon-gamma (IFN-γ), whose release in vivo is generally stimulated by the tumor presence and aims at rejecting the tumor itself [ 59 ]. The EV destruction by perforin may liberate ADO in the TME, as detected by a sophisticated procedure coupling liquid chromatography to mass spectrometry analysis (LC-MS), which in turn hinders perforin secretion by CTLs.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are cell‐derived membranous particles of sub‐micrometre sizes that play important roles in cancer biology by mediating intercellular communication through carrying proteins, nucleic acids, and lipids (Reategui et al., 2018; Tadokoro et al., 2020; Wan et al., 2018). EVs comprise many subtypes, including exosomes, microvesicles, and apoptotic bodies (Wang, Tan, & Guan, 2019).…”
Section: Introductionmentioning
confidence: 99%